Use of cognitive enhancers and associated medical care costs among patients with dementia: a nationwide study in Taiwan. (May 2014) - Ku, Li-Jung E.; Pai, Ming-Chyi
ABSTRACT Background: Pharmaceutical therapy for patients with dementia including cholinesterase inhibitors (ChEI) and memantine is covered by Taiwan's National Health Insurance (NHI) but with strict reimbursement criteria. This study compared utilization of selected cognitive enhancers among elderly patients with dementia and estimated associated differences in medical care costs. Methods: This study used medical claims and pharmacy claims from the NHI Research Database of Taiwan from 2009 to 2011, which included all patients 65 years or older diagnosed with dementia in their outpatient or inpatient claims. Both individual-level and market-level analysis were performed to calculate the average medical costs per person and the share of drug expenditures. Generalized linear models with propensity score adjustment estimated differences in medical care costs by use of selected cognitive enhancers. Results: Users of ChEI had the highest medication and outpatient costs but the lowest inpatient costs among all users of cognitive enhancers. However, annual adjusted total medical care costs per ChEI user were not significantly different from those who used cerebral vasodilators (CBV). In 2011, 52.4% of the elderly with dementia in Taiwan used cognitive enhancers, but among them 88.3% used CBV while 9.2% used ChEI. Among patients with dementia who used at least one cognitive enhancer, the aggregated expenditure as a share of their total drug expenditures was 9.7% in 2011. Conclusion: Given that CBV had a much higher utilization rate than ChEI or memantine among elderly people with dementia, the strict reimbursement policy for ChEI and memantine may need to be revisited to increase access to those drugs by patients with dementia in Taiwan.